Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.orglett.7b03939
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diels–Alder Reaction of α,β-Unsaturated Oxazolidin-2-one Derivatives Catalyzed by a Chiral Fe(III)-Bipyridine Diol Complex

Abstract: An asymmetric Fe-bipyridine diol catalyzed Diels-Alder reaction of α,β-unsaturated oxazolidin-2-ones has been developed. Among various Fe/Fe salts, Fe(ClO)·6HO was selected as the Lewis acid of choice. The use of a low catalyst loading (2 mol % of Fe(ClO)·6HO and 2.4 mol % of Bolm's ligand) afforded high yields (up to 99%) and high enantiomeric excesses (up to 98%) of endo-cycloadducts for the Diels-Alder reaction between cyclopentadiene and substituted acryloyloxazolidin-2-ones. Other noncyclic dienes led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…The best compromise is obtained with complex 1‐Me,Et , which exhibits TOF = 1.4 min –1 and TON = 111. The set of results justifies the increased interest that iron complexes receive in catalysis today, under both homogeneous and heterogeneous conditions.…”
Section: Discussionmentioning
confidence: 56%
“…The best compromise is obtained with complex 1‐Me,Et , which exhibits TOF = 1.4 min –1 and TON = 111. The set of results justifies the increased interest that iron complexes receive in catalysis today, under both homogeneous and heterogeneous conditions.…”
Section: Discussionmentioning
confidence: 56%
“…In 2018, Ollevier et al demonstrated that a chiral iron catalyst, in situ generated from Fe(ClO 4 ) 2 and chiral bipyridine diol ligand ent-99 in acetonitrile, was able to promote highly enantioselectively the Diels-Alder cycloaddition of 3-acryloyloxazolidinones 100 with cyclic dienes 120 [90]. For example, the reaction of cyclopentadiene (n = 1) with various 3-acryloyloxazolidinones 100 afforded the corresponding chiral endo-cycloadducts 121 in high yields (70-95%), moderate to high diastereoselectivities (48-88% de) and low to excellent enantioselectivities (12-98% ee) by using low catalyst loadings (2.4-4.8 mol%), as shown in Scheme 48.…”
Section: Enantioselective Cyclizationsmentioning
confidence: 99%
“…However, ligand lability can still be a problem, and is further exacerbated for metal ions with low or no crystal field stabilization (e.g., high‐spin d 5 centers). Unfortunately, this list includes Fe 3+ complexes whose extensive role in homogeneous catalysis has been recognized for a long time . Clearly, the field of specialty chiral chemicals stands to benefit from the availability of new, nonracemizable Fe 3+ enantiopure compounds.…”
Section: Figurementioning
confidence: 99%